2008
DOI: 10.1111/j.1742-6723.2008.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability of the Australasian Triage Scale for mental health patients

Abstract: There is a need to develop and implement a validated, standardized national triage tool for mental health patients. The ATS per se is insufficient to ensure acceptable interrater reliability, particularly during busy periods in the ED, and between states. Given the influence the ATS has on key outcomes, it is imperative for this tool to be robust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 8 publications
0
43
0
Order By: Relevance
“…7 The inter-rater reliability of the ATS for mental health patients in ED is particularly inadequate. 8 The triage category assigned can, in part, depend on the person doing the triage. For example, the results of a review of the literature (involving eight studies) suggest that triage nurses who have received triage education make better triage decisions whereas none of the studies found a significant relationship between triage decision-making and experience, either the number of years working as an emergency nurse or years of triage experience.…”
Section: Discussionmentioning
confidence: 99%
“…7 The inter-rater reliability of the ATS for mental health patients in ED is particularly inadequate. 8 The triage category assigned can, in part, depend on the person doing the triage. For example, the results of a review of the literature (involving eight studies) suggest that triage nurses who have received triage education make better triage decisions whereas none of the studies found a significant relationship between triage decision-making and experience, either the number of years working as an emergency nurse or years of triage experience.…”
Section: Discussionmentioning
confidence: 99%
“…However, psychiatric assessment of many mental disorders has low inter-rater concordance particularly with respect to personality disorders [42]. The criteria for evaluating criminal responsibility are based on the individual's ability to make a distinction between right and wrong and to counter impulse; such abilities are absent in some psychiatric disorders resulting in exemption or a more lenient sentencing.…”
Section: Application Of Genetic and Neuroimaging Findings In The Forementioning
confidence: 99%
“…A national tool to triage mental health consumers has been suggested (Broadbent et al . 2007; Creaton et al . 2008; Kinner et al .…”
Section: Key Findingsmentioning
confidence: 99%